Acute Vs Delayed ACL Reconstruction. Early Differences and Preliminary Two Year Results: A Randomized Controlled Trial - Eriksson, Karl (Orthop J Sports Med, 2016)
OBJECTIVES: Historically acute ACL reconstruction has been avoided due to reports of early rehabilitation problems with stiffness. Are these reports still valid today with modern arthroscopic techniques? METHODS: 70 patients with a high recreational activity level (Tegner ≥6) who presented with a acute ACL injury were randomized to an acute reconstruction within 8 days from the injury or delayed reconstruction after 6-10 weeks. Four surgeons performed the ACL reconstructions with quadrupled semitendinosus tendon grafts and endobutton and metallic interference screw fixation. The rehabilitation training was performed at the same physiotherapy center for all patients. The follow up at 6 and 24 months included ROM, Lachman, Rolimeter, pivot shift, one leg hop, IKDC, KOOS, Lysholm and Tegner activity level. RESULTS: There were no differences between the groups in ROM, IKDC, activity level or laxity at 6 months. Four patients had a combined extension and flexion deficit of more than 15 degrees, two from each group. In the acute group 79% had an objective IKDC grade A or B compared with 73% in the delayed group. The one leg hop index above 90% was found in 50% in the acute group and 24% in the delayed group (p=0.04). Functional data for the 2-year follow up are not available at the time of abstract writing. The median activity level according to Tegner was restored to pre-injury levels in both groups after one year, and was stationary at 2 years. The visual analogue scale (VAS) response to the question “How is your knee working on a scale from 0-100? (100 = best)” revealed 81 in the acute and 71 in the delayed group (p=0.1). To the question “How does your knee affect your activity level on a scale from 0-100? (100 = no affection)” the mean score was 75 in the acute group and 67 in the delayed group (p=0.3). At one and two years the KOOS was statistically similar between the groups but with slightly higher subscale “Sport and recreation” scores, 85 in the acute group at 2 years compared to 78 in the delayed group (p=0.2). At the meeting preliminary results regarding functional tests and additional procedures for the groups will be presented. CONCLUSION: No negative effects of an acute ACL reconstruction were found at 6 months follow up. Preliminary 2 year results point in the same direction. Acute reconstruction of the ACL seems to be safe and a potential benefit might be decreased loss of muscle function. Further analysis of the 2 year results is needed before final conclusions can be drawn.